Effect of stress inoculation training on coping styles and psychological well-being status of mothers with mental retard children - Jahanshir Tavakolizadeh; Zeynab Mohammadi; Somayeh Safarzade (Gonabad University of Medical Sciences, 2017)
Mental retardation is one of the most significant problems of human society among children and adolescents. It puts families, especially mothers, under a lot of stress and threatens their mental health. The initial purpose of this study was to determine the effect of stress inoculation training on coping styles and psychological well-being status in women who have children with mental retardation. In this quasi-experimental study, 30 participants were randomly were selected by simple sampling method that were assigned into the experimental and control groups. The statistical population comprised the mothers who have children with mental retardation at the training center. Ryff scales of psychological well-being and coping inventory for stressful situations and psychological well-being scale were implemented before and after the stress inoculation training (presented only for the experimental group in eight sessions). The results of the statistical analysis showed that the training increased the problem-oriented coping style and decreased the avoidant and emotional coping styles. Thus, the results demonstrated that stress inoculation training was effective in stress coping and improving psychological well-being in mothers. According to the obtained finding, psychological well-being scores in the experimental group were remarkably different from those in the control group. Based on these results, it is recommended for the experts in the field to use stress inoculation training to decrease stress and enhance psychological well-being of mothers.